Clinico-Epidemiological Characteristics of Patients With Inflammatory Bowel Disease in Egypt: A Nationwide Multicenter Study - Elbadry, Mohamed; Nour, Mohamed O.; Hussien, Mohamed; Ghoneem, Elsayed Awad; Medhat, Mohammed A.; Shehab, Hany; Galal, Sherif; Eltabbakh, Mohamed; El-Raey, Fathiya; Negm, Mohamed; Afify, Shimaa; Abdelhamed, Walaa; et al. (Frontiers in Medicine, 2022)
Background and aims: Ulcerative colitis (UC) and Crohn's disease (CD) are the most common types of Inflammatory bowel disease (IBD), with unsatisfactory responses to traditional therapies and a worsening prognosis. In Egypt and most developing countries, the lack of recent epidemiological and prognostic data adversely affects management strategies. We collected and analyzed data of IBD patients from multiple centers across Egypt to evaluate patients’ clinical and epidemiological characteristics. Methods: This retrospective multicenter study included patients diagnosed with IBD between May 2018 and August 2021, at 14 tertiary gastroenterology units across Egypt. Record analysis addressed a combination of clinico-epidemiological characteristics, biochemical tests, stool markers, endoscopic features, histological information, and different lines for IBD treatment. Results: We identified 1104 patients with an established diagnosis of IBD; 81% of them had UC, and 19% showed CD. About 19.8% displayed comorbid conditions, primarily associated with CD. The most frequent complaints were diarrhea (73.2%), rectal bleeding (54.6%, significantly higher among UC patients), and 46.8% with abdominal pain (more often with CD). Conventional therapy was effective in treating 94.7% of patients. The main lesion in CD patients was ileal (47.8%); UC patients mainly exhibited proctosigmoiditis (28.4%). Dysplasia was detected in 7.2% of patients, mainly subjects with UC. Conclusions: To our knowledge, our effort is the first and largest cohort of Egyptian IBD patients to describe clinical and epidemiological characteristics, and diagnostic and management approaches. More extensive prospective studies are still needed to fully characterize disease distribution, environmental factors, and pathological features of the disease.